The radial and azimuthal profiles of Mg II absorption around 0.5 < z < 0.9 zCOSMOS galaxies of different colors, masses and environments - Bordoloi, R; Lilly, S; Knobel, C; Bolzonella, M; Kampczyk, P; Carollo, C; Iovino, A; Zucca, E; Contini, T; Kneib, J; Fevre, O; Mainieri, V; et al. (Institute of Physics Publishing, 2011)
We map the radial and azimuthal distribution of Mg II gas within 200 kpc (physical) of 4000 galaxies at redshifts 0.5 < z < 0.9 using co-added spectra of more than 5000 background galaxies at z > 1. We investigate the variation of Mg II rest frame equivalent width as a function of the radial impact parameter for different subsets of foreground galaxies selected in terms of their rest-frame colors and masses. Blue galaxies have a significantly higher average Mg II equivalent width at close galactocentric radii as compared to the red galaxies. Amongst the blue galaxies, there is a correlation between Mg II equivalent width and galactic stellar mass of the host galaxy. We also find that the distribution of Mg II absorption around group galaxies is more extended than that for non-group galaxies, and that groups as a whole have more extended radial profiles than individual galaxies. Interestingly, these effects can be satisfactorily modeled by a simple superposition of the absorption profiles of individual member galaxies, assuming that these are the same as those of non-group galaxies, suggesting that the group environment may not significantly enhance or diminish the Mg II absorption of individual galaxies. We show that there is a strong azimuthal dependence of the Mg II absorption within 50 kpc of inclined disk-dominated galaxies, indicating the presence of a strongly bipolar outflow aligned along the disk rotation axis. There is no significant dependence of Mg II absorption on the apparent inclination angle of disk-dominated galaxies.